Brain Cortex Activity in Children With Anterior Open Bite: A Pilot Study. (2020)
The aim of this study was to determine the activity of the brain cortex of children with AOB at rest and during phonation and deglutition and to evaluate the association of intelligence quotient (IQ), attention (Test of Variables of Attention, known as TOVA), beats per minute (BPM), and oxygen saturation measurement (SpO2) with brain activity in subjects with AOB.